A Neuron-Targeted Nanoparticle for siRNA Delivery to Traumatic Brain Injuries - Kwon, Ester J. (ACS Nano, 2016)
Traumatic brain injuries (TBIs) affect 2.5 million Americans per year and survivors of TBI can develop long-term impairments in physical, cognitive, and psychosocial functions. Currently, there are no treatments available to stop the long-term effects of TBI. Although the primary injury can only be prevented, there is an opportunity for intervention during the secondary injury, which persists over the course of hours to years after the initial injury. One promising strategy is to modulate destructive pathways using nucleic acid therapeutics, which can downregulate “undruggable” targets considered difficult to inhibit with small molecules; however, the delivery of these materials to the central nervous system is challenging. We engineered a neuron-targeting nanoparticle which can mediate intracellular trafficking of siRNA cargo and achieve silencing of mRNA and protein levels in cultured cells. We hypothesized that soon after an injury, nanoparticles in the bloodstream may be able to infiltrate brain tissue in the vicinity of areas with a compromised blood brain barrier (BBB). We find that, when administered systemically into animals with brain injuries, neuron-targeted nanoparticles can accumulate into the tissue adjacent to the injured site and downregulate a therapeutic candidate.